2015
DOI: 10.3906/sag-1405-43
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HCV genotype 4d infections in Kayseri, Turkey*

Abstract: It is estimated that 130-210 million people worldwide are chronically infected with the hepatitis C virus (HCV). Complications of chronic liver disease, like cirrhosis with or without hepatocellular carcinoma, will develop over many years in around 20% of these patients, making HCV infections a major public health issue (1).HCV has six major genotypes and more than 80 subtypes (2). Recently a seventh genotype was proposed (3). Genotypes may differ in their epidemiology, pathogenesis, and response to treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…In Turkey, genotype 4 distribution does not show high variability among the regions, ranging between 0.5% and 3.4% (Table 3), while a significant prevalence described only in Kayseri (32%) (13). By using molecular clock analysis, they predicted the introduction of type 4d HCV into the Kayseri region probably 30-75 years ago (26). The prevalence of genotype 3 is globally higher in the intravenous drug users (9).…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, genotype 4 distribution does not show high variability among the regions, ranging between 0.5% and 3.4% (Table 3), while a significant prevalence described only in Kayseri (32%) (13). By using molecular clock analysis, they predicted the introduction of type 4d HCV into the Kayseri region probably 30-75 years ago (26). The prevalence of genotype 3 is globally higher in the intravenous drug users (9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in different localities of Turkey reported genotype 4 rates in the range 0.6–35.6% . The rates in Central Anatolia region were the highest; 28–35.6%, but still significantly lower (1.6%) than the rate detected in Aydin province (Table ).…”
Section: Discussionmentioning
confidence: 74%
“…Patients with genotype 4 were interestingly all males. In a study from Kayseri region, approximately two‐thirds of the patients infected with HCV genotypes 1 and 4 were female; however, most patients infected with genotype 2 were male .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This alteration may be due to immigrants, touristic activities and different risk factors for HCV infection, as well as increased safety procedures in medical practice. Table 4 shows the results of some of the HCV genotyping studies in Turkey (13,14,15,16,17,18,19,20,21,22,23,24,25,26,27).…”
Section: Discussionmentioning
confidence: 99%